2022
DOI: 10.1186/s12888-021-03679-0
|View full text |Cite
|
Sign up to set email alerts
|

Mental health status among prison officers in the process of enforcing the law during COVID-19epidemic: a cross-sectional survey from China

Abstract: Background A global public health emergency triggered by the Coronavirus Disease 2019 (COVID-19) epidemic may have are markable psychological impact on the population. There is still limited psychological research on police officers, especially prison officers in the process of enforcing the law. The present study aims to identify prevalence and influencing factors on mental health status among frontline prison officers in China during the prevention and control of the COVID-19 epidemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(54 reference statements)
0
3
1
2
Order By: Relevance
“…Thus, compared to the pre-COVID-19 stage, our findings might indicate a higher prevalence of anxiety and depressive symptoms among prison officers than previous studies. Meanwhile, compared to the research conducted at the COVID-19 outbreak’s onset, our study’s results are also significantly higher than those of prison officers in China (33.43%) and in the United States (38, 32%), as mentioned above ( 24 , 25 ). Moreover, the mental health status of prison officers in this study was worse than that of other groups in China—including older adults, perinatal women, and medical residents ( 40 , 41 , 54 )—who were also evaluated during the prolonged COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Thus, compared to the pre-COVID-19 stage, our findings might indicate a higher prevalence of anxiety and depressive symptoms among prison officers than previous studies. Meanwhile, compared to the research conducted at the COVID-19 outbreak’s onset, our study’s results are also significantly higher than those of prison officers in China (33.43%) and in the United States (38, 32%), as mentioned above ( 24 , 25 ). Moreover, the mental health status of prison officers in this study was worse than that of other groups in China—including older adults, perinatal women, and medical residents ( 40 , 41 , 54 )—who were also evaluated during the prolonged COVID-19 pandemic.…”
Section: Discussioncontrasting
confidence: 59%
“…During the COVID-19 outbreak’s initial stages, several studies investigated prison officers’ mental health status. Li et al employed the 12-item General Health Questionnaire (GHQ-12) to survey Western Chinese frontline prison officers, finding that mental health issues’ prevalence was 33.43% ( 24 ). According to data from US correctional facilities, approximately 32% of correctional officers reported mild-to-severe depression symptoms, while 38% expressed mild-to-severe anxiety symptoms ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…코로나19 대유행 시기 모든 근로자는 고용불안과 함께 과중한 업무량, 코로나19 감염 위험, 적절한 휴식 부재 등으로 강한 심리적 압박을 경험하였다 [9][10][11]. 직장 및 생활의 부정적 변화는 근로자의 적응을 방해하고 작업 효율성을 낮추며 전반적인 삶의 질을 저하시켰다 [9] [12]. 선행연구에 따르면, 근로자의 코로나19에 대한 두려움이 스트레스와 이직의도, 퇴사를 증가시켰고, 더 나아가 불안, 우울, 공황, 외상 후 스트레스와 같은 정신건강 문제와 밀접하게 관계되었음이 밝혀졌다 [9] [11][12][13].…”
Section: 서론unclassified
“…직장 및 생활의 부정적 변화는 근로자의 적응을 방해하고 작업 효율성을 낮추며 전반적인 삶의 질을 저하시켰다 [9] [12]. 선행연구에 따르면, 근로자의 코로나19에 대한 두려움이 스트레스와 이직의도, 퇴사를 증가시켰고, 더 나아가 불안, 우울, 공황, 외상 후 스트레스와 같은 정신건강 문제와 밀접하게 관계되었음이 밝혀졌다 [9] [11][12][13]. 코로나19 두려움이 높은 근로자일수록 우울 증상이 더욱 심각하였다 [9].…”
Section: 서론unclassified
“…One study found that Chinese prison police have a high prevalence of depression, with approximately 72.6% having depressive symptoms (Zeng et al, 2023). Emerging studies have shown that prison staff exhibit significant anxiety, depressive symptoms, and feel significant stress during the lockdown of COVID-19 (Burhanullah et al, 2022; Y. Li et al, 2022); consequently, it is of great relevance to study the mental health of prison police.…”
Section: Introductionmentioning
confidence: 99%